Pengaruh Penggunaan Bahasa Gaul Terhadap Kemurnian Bahasa Indonesia di Kalangan Remaja (Universitas Muhammadiyah Maumere) - Antonia Gianditta Astrella; Yeremias Bardi; Azyumardi Azra; Serlina Hadijah Lia; Clemens Belang Kabelen; Maria Yuliana Nona Yati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Slang is a form of language that develops among teenagers, especially in urban environments, which often combines foreign elements or modifications of Indonesian. This research aims to identify the influence of the use of slang on the purity of Indonesian among teenagers. The main focus in making research is how the use of slang can have a positive and negative impact on Indonesian language skills in accordance with standard rules and structures. The research method used is qualitative with a descriptive approach, through interviews and observations of teenagers who often use slang. The research results show that although slang enriches vocabulary and provides space for self-expression, excessive use of slang can interfere with correct understanding of Indonesian, especially in formal communication contexts. Therefore, a balance between the use of slang and standard Indonesian is very necessary, especially among teenagers, to maintain the purity of the Indonesian language.